Modelling phase-transition-driven gas dispersion resulting from supercritical CO2 pipeline leak in complex terrain - Xinhong Li; Changzhi Bi; Cheng Li; Hanyu Liu; Fei Shi; Peihua Liu; Ziyue Han (Process Safety and Environmental Protection, 2026)

Assessing the impacts of reclaimed water replenishment on riverine aquatic biodiversity using environmental DNA metabarcoding - Fei Zhao; Tao Chen; Shujian Wu; Dong Chen; Yihua Xiao; Penghao Wei; Xuejun Bi; Yiwei Wang; Liqun Chen; Guo Li; Xueqing Shi; How Yong Ng (Journal of Environmental Management, 2026)

Numerical Investigation of Time-Dependent Deformation and Fracture Evolution in Flawed Sandstone - Teng-Fei Fu; Zhu-Guang Wang; Bi-Bi Qiao; Ya-Tao Li; Tao Ding; Chong-Feng Chen (Geotechnical and Geological Engineering, 2026)

Organic fertilization alleviates soil sickness in monoculture systems by driving pathogen-suppressive rhizosphere community assembly - Tong Peng; Chuanji Zhang; Xiaoqi He; Zhenyu Cheng; Junjie Li; Yanfang Song; Ziyu Liu; Meiyun Pu; Yi Yan; Panshuai Fei; Yurong Bi; Xiaofan Na (Plant and Soil, 2026)

Immunogenicity and safety of an Escherichia coli-produced 9-valent HPV vaccine in adolescents aged 9 to 17 compared with young women - Yulin Jing; Xiaowen Hu; Li Zhang; Jiangyahui Wang; Fei Yang; Rong Wang; Ying Jiang; Lingling Nie; Zhongqiang Jin; Xuecheng Liu; Sihai Li; Chao Du; et al. (Science Bulletin, 2026)

Design and activity validation of GABA-gated chloride channels allosteric modulators based on computational biology - Siyi Yang; Shuang Gao; Tiansong Li; Jinghu Bi; Ying Fu; Fei Ye (Pesticide Biochemistry and Physiology, 2026)

Algal ecological dynamics tracking model for studying hydrodynamic impacts on algae transport and accumulation in a shallow lake - Fei Du; Xiaobo Liu; Shiyan Wang; Chang Liu; Aiping Huang; Weijie Wang; Budong Li; Rui Gao; Xin Tian; Zhen Han; Hao Fan; Bi Wu (Journal of Hydrology, 2026)

Dissection of the genetic basis of 1392 rice landraces and 770 hybrid combinations reveals great potential of rice landraces in hybrid rice improvement - Yinting Wang; Zixuan Li; Bi Wu; Xueqiang Wang; Wenyan Yang; Danjing Lou; Jinyue Ge; Ziran Liu; Wenlong Guo; Neng Zhao; Jun Yang; Weiya Fan; et al. (Molecular Plant, 2026)

Investigating the role of potato protein isolate in high internal phase emulsions for 3D printing ink applications - Chong-hao Bi; Ao-xue Qie; Fei Gao; Quan-lai Li; Bin Tian; Xiao-rong Sun (Food Hydrocolloids, 2025)

Male and Female Parent Birds Enhance Their Reproductive Success Using Different Strategies but the Same Optimal Pathway - Ning‐Ning Sun; Bi‐Yun Jia; Rong‐Yu Xu; Li‐Fang Gao; Xue‐Fei Guo; Rang Li; Yu‐Jie Wang; Shu‐Min Wang; Bo Du (Molecular Ecology, 2025)
Parental birds exhibit diverse alternative reproductive strategies; however, the pathways by which these alternative strategies enhance the reproductive success of parents remain poorly understood. Here, we used generalised linear mixed models (GLMMs) and structural equation modelling (SEM) to analyse a long‐term dataset of multiple components of reproductive fitness in the azure‐winged magpie ( Cyanopica cyanus ), including incipient offspring number, extra‐pair fertilisation (EPF), unhatched eggs, offspring preyed on by predators and conspecific raiders and offspring that starved. GLMM results revealed significant associations between these components and the first lay date. SEM further elucidated causal relationships among female/male breeding conditions, cooperative breeding, first lay date and the positive/negative effects on female/male reproductive success. SEM results revealed that both female and male reproductive success were mainly influenced by negative effects rather than positive effects. Specifically, negative effects were largely determined by unhatched eggs for females but by female EPF frequency for males. In contrast, positive effects were predominantly determined by the incipient offspring number for both sexes. Therefore, minimising negative effects was prioritised over enhancing positive effects to achieve reproductive success in both sexes. To modulate these effects, females and males employed different strategies. However, they achieved their respective goals through a shared pathway: reducing negative effects for social bonds formed with smaller‐bodied males and enhancing positive effects for social bonds formed with larger‐bodied males. Our multivariate analysis of various aspects of avian reproduction suggests that the formation of social bonds plays a more important role than alternative reproductive strategies in determining individual reproductive success.

Association of GRM7 Polymorphisms with Bilateral Auditory Regions Glutamate and Coupling with Glutathione in ARHL Patients - Jing Wang; Fuyan Li; Fuxin Ren; Wen Ma; Yuxi Liu; Wenjing Zhang; Xi Li; Yanfei Bi; Qian Xin; Fei Gao (Molecular Neurobiology, 2025)

7-Hydroxylathyrol defeats geminivirus through targeting C4 and activating host defense - Bi Wang; Xiaoxiao Xu; Wenhao Liang; Tong Shi; Qizhi Wang; Yu Chen; Sha Chen; Fei Liu; Linwei Li (Pesticide Biochemistry and Physiology, 2025)

Ratiometric fluorescent nanoprobes based on lanthanide coordination polymers for visual intelligent detection of phosphate - Yongxin Li; Rongrong Zhou; Fei Xue; Ning Bi; Lina Zhang; Qianyang Li; Kai Shi; Jiang Wu; Lei Jia; Jun Xu (Chemical Engineering Journal, 2025)

UV-B stress reshapes root-associated microbial communities and networks, driven by host plant resistance - Chuanji Zhang; Na Gao; Xiaofan Na; Kaile Li; Meiyun Pu; Hao Sun; Yanfang Song; Tong Peng; Panshuai Fei; Junjie Li; Zhenyu Cheng; Xiaoqi He; et al. (Soil Biology and Biochemistry, 2025)

The synthesis of arylmethylene bisindoles catalyzed by nickel perchlorate as potential antifungal agent against Clarireedia homoeocarpa - Ye Zhou; Ruyuan Wang; Rui Feng; Bi Wang; Shu Xu; Mei Tian; Wenhao Liang; Jin Chen; Yu Chen; Xu Feng; Li Lin; Jinyue Luo; et al. (Phytochemistry Letters, 2025)

Removal of ciprofloxacin by PAA-PAM hydrogel: Adsorption performance and mechanism studies - Man Gao; Mengmeng Sun; Jingtao Bi; Shizhao Wang; Xiaofu Guo; Fei Li; Jie Liu; Yingying Zhao (Journal of Water Process Engineering, 2025)

Effect of ultrasound intervention timing on the formation mechanism and emulsifying properties of chickpea protein isolate-citrus pectin complexes - Zhi-gang Huang; Guo-liang Zhang; Ao-xue Qie; Quan-lai Li; Chonghao Bi; Fei Gao (Food Chemistry, 2025)

Design and performance investigation of novel efficient photocatalysts PVP-modified PVDF/BiOBr photocatalytic membranes for wastewater treatment - Fei Bi; Zhemei Zheng; Rongrong Li; Ruiying Du; Li Zhao; Shanshan Xiao; Liyan Wang; Xiangting Dong (Chemical Engineering Journal, 2025)

Energy-free and ultrafast nano pump of water - Chun Li; Dongdong Zhou; Fei Zheng; Yujuan Wang; Kedong Bi (Chemical Engineering Journal, 2025)

Exposure to multiple metals and leukocyte telomere length in children and adolescents: The mediating effect of thyroid hormones - Qing Liu; Gaojie Fan; Jianing Bi; Qing Fang; Fei Luo; Xiaofeng Huang; Heng Li; Binghai Liu; Lianyan Yan; Wenwen Guo; Liqin Hu; Surong Mei; et al. (Environmental Research, 2025)

Features of particle-phase PAHs from traffic emissions using tunnel measurement and urban roadside observation in China - Fei Gao; Zhitao Cai; Zhenyu Luo; Junchao Zhao; Songxin Zheng; Li Wang; Bi Chen; Kebin He; Huan Liu (Environmental Pollution, 2025)

Quality control and improvement of GNSS-IR soil moisture robust inversion model - Yijie Li; Linyu Luo; Fei Guo; Furong Yang; Tianyang Wang; Hang Gao; Xinyu Bi; Zhitao Zhang; Yifei Yao (Advances in Space Research, 2025)

Alteromonas arenosi sp. nov., a novel bioflocculant-producing bacterium, isolated from intertidal sand - Bi Luo; Jing-Yun Su; Ya-Fei Zhang; Yong-Hui Xiao; Yun-Lin Peng; Mei-Ling Sun; Yi Li (Antonie van Leeuwenhoek, 2024)

Plasma-induced surface interactions of Pd/SrTiO3 catalyst for improved performance of photocatalytic degradation of toluene - Dongliang Gao; Bingwei Wang; Jingyue Bi; Fan Xue; Mifen Cui; Zhaoyang Fei; Lei Li; Xu Qiao (Journal of Environmental Chemical Engineering, 2024)

Association of exposure to multiple metals with hemoglobin levels in Chinese children and adolescents - Fei Luo; Jianing Bi; Qing Liu; Gaojie Fan; Qing Fang; Xiya Qin; Xukuan Zhang; Xiaofeng Huang; Heng Li; Wenwen Guo; Binghai Liu; Lianyan Yan; et al. (Science of The Total Environment, 2024)

The mechanism of interaction between tri-para-cresyl phosphate and human serum protein: A multispectroscopic and in-silico study - Shang-Chun Li; Han Xu; Peng-Fei Wang; Li-Mei Wang; Yue-Rou Du; Yong-Bin Guan; Zhi-Xia Han; Qing-Bi Zhang (Chemico-Biological Interactions, 2024)

3D reconstruction and characterization of cotton bolls in situ based on UAV technology - Shunfu Xiao; Shuaipeng Fei; Yulu Ye; Demin Xu; Ziwen Xie; Kaiyi Bi; Yan Guo; Baoguo Li; Rui Zhang; Yuntao Ma (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

An integrated linguistic Pythagorean fuzzy decision-making approach for risk analysis of offshore wind turbine - Jinfeng Li; Chencan Bi; Fei Gao; Weikai He (Ocean Engineering, 2024)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Undescribed steroidal alkaloids from the bulbs of Fritillaria sinica - Jia-yuan Li; Shi-fei Wu; Ya-ling An; Chang-liang Yao; Shuai Yao; Yong Huang; Wen-long Wei; Jian-qing Zhang; Qi-rui Bi; Hua Qu; De-an Guo (Phytochemistry, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Safety assessment of organic micropollutants in reclaimed water: Chemical analyses, ecological risk assessments, and in vivo endocrine-disrupting studies - Fei Zhao; Yinfei Hao; Qianru Xu; Zhineng Hao; Xinhui Li; Lihua Cheng; Dong Chen; Xueqing Shi; Yihua Xiao; Penghao Wei; Xuejun Bi (Science of The Total Environment, 2023)

High-throughput calculation of organ-scale traits with reconstructed accurate 3D canopy structures using a UAV RGB camera with an advanced cross-circling oblique route - Shunfu Xiao; Yulu Ye; Shuaipeng Fei; Haochong Chen; Bingyu zhang; Qing li; Zhibo Cai; Yingpu Che; Qing Wang; AbuZar Ghafoor; Kaiyi Bi; Ke Shao; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Shewanella subflava sp. nov., a novel multi-resistant bacterium, isolated from the estuary of the Fenhe River into the Yellow River - Bi Luo; Jing-Yun Su; Ya-Nan Wang; Li Guan; Kai-Shi Dong; Hui-Jing Niu; Shao-Fei Shen; Yi Li (Antonie van Leeuwenhoek, 2023)

Bipolar membrane electrodialysis combined with ozone oxidation wet scrubbing to remove SO2 and NO from flue gas and achieve CO2 mineralization - Yingying Zhao; Yupeng Cheng; Tingting Zhang; Shizhao Wang; Xiaofu Guo; Junsheng Yuan; Zhiyong Ji; Jie Liu; Fei Li; Jing Wang; Jingtao Bi (Fuel, 2023)

Energy Evolution Characteristics of Sandstones During Confining Pressure Cyclic Unloading Conditions - Yu Zhao; Shuang Dang; Jing Bi; Chaolin Wang; Fei Gan; Jiashen Li (Rock Mechanics and Rock Engineering, 2023)

Identification and validation of core microbes associated with key aroma formation in fermented pepper paste (Capsicum annuumL.) - Meilun Li; Xinxing Xu; Shuang Bi; Xin Pan; Fei Lao; Jihong Wu (Food Research International, 2023)

Dental follicle cells show potential for treating Parkinson’s disease through dopaminergic-neuronogenic differentiation - Fei Bi; Jie Xiong; Xue Han; Chao Yang; Xinghan Li; Guoqing Chen; Weihua Guo; Weidong Tian (Human Cell, 2022)

Integrative analysis of the pharmaceutical active ingredient and transcriptome of the aerial parts of Glycyrrhiza uralensis under salt stress reveals liquiritin accumulation via ABA-mediated signaling - Quan Bi; Hua Yao; Fei Wang; Dajun He; Wenbin Xu; Shuangquan Xie; Xifeng Chen; Yuxia Li; Hailiang Liu; Haitao Shen; Hongbin Li (Molecular Genetics and Genomics, 2022)
The aerial parts of Glycyrrhiza uralensis supply substantial raw material for the extraction of active pharmaceutical ingredients comprehensively utilized in many industries. Our previous study indicated that salt stress increased the content of active ingredients. However, the regulatory mechanism remains unclear. In this study, RNA-sequencing (RNA-seq) of the aerial parts of G. uralensis treated with 150 mM NaCl for 0, 2, 6, and 12 h was performed to identify the key genes and metabolic pathways regulating pharmacological active component accumulation. The main active component detection showed that liquiritin was the major ingredient and exhibited more than a ten-fold significant increase in the 6 h NaCl treatment. Temporal expression analysis of the obtained 4245 differentially expressed genes (DEGs) obtained by RNA-seq revealed two screened profiles that included the significant up-regulated DEGs (UDEGs) at different treatment points. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis of these UDEGs identified phenylpropanoid metabolism and flavonoid biosynthesis as the most significantly enriched pathways in 2 h treated materials. Interestingly, the carotenoid biosynthesis pathway that is related to ABA synthesis was also discovered, and the ABA content was significantly promoted after 6 h NaCl treatment. Following ABA stimulation, the content of liquiritin demonstrated a significant and immediate increase after 2 h treatment, with the corresponding consistent expression of genes involved in the pathways of ABA signal transduction and flavonoid biosynthesis, but not in the pathway of glycyrrhizic acid biosynthesis. Our study concludes that salt stress might promote liquiritin accumulation through the ABA-mediated signaling pathway, and provides effective reference for genetic improvement and comprehensive utilization of G. uralensis .

Discerning the Putative U and V Chromosomes of Saccharina japonica (Phaeophyta) by Cytogenetic Mapping of Sex-Linked Molecular Markers - Yu Du; Peng-Fei Liu; Zhi Li; Qian Zheng; Yan-Hui Bi; Zhi-Gang Zhou (Frontiers in Marine Science, 2022)
Saccharina japonica , an importantly industrial species in brown seaweeds, has a typical alternate life history of heteromorphic generations and UV sex determination system. But up to now, the sex chromosomes, U and V, in this kelp remain to be evidenced cytologically. In the present study, the female-linked (SJ-f_000170 and MSj68-58-2) and male-linked (SJ-13_001840 and MSj68-16-2) molecular markers developed on the basis of Ectocarpus sex-determining regions (SDRs) were selected after PCR amplification and Southern blotting analysis. Mono-color fluorescence in situ hybridization (FISH) to the kelp metaphase chromosomes with each of these confirmed sex-linked markers as a probe indicated that the hybridization signals were confined to either female or male gametophytes exclusively. The shape and size of hybridized chromosomes and the relative location of these sex-linked markers on them suggested that the marked chromosomes in a sex were the same, which was further confirmed by dual-color FISH observations. SJ-f_000170 and SJ-13_001840, corresponding to each sex, were therefore used to map the sporophyte metaphase chromosomes by dual-color FISH technique, and they were hybridized on different chromosomes as expected. The sporophyte metaphase chromosomes as hybridized by SJ-f_000170 and SJ-13_001840 resembled those in either female or male gametophytes, suggesting that they were the putative U and V, respectively, chromosomes in S . japonica . To further demonstrate the reliability of this inference, genomic information of the screened bacterial artificial chromosome (BAC) clones carrying two female-linked markers, for example, from the constructed BAC libraries of the kelp female gametophytes was provided. The insert sequencing of two selected BAC clones revealed that repetitive elements were rich whereas gene density was poor, which was characterized as non-recombining SDR sequences in brown seaweed Ectocarpus sp. and liverwort Marchantia polymorpha . The present study laid a solid foundation for unveiling the mystery of S . japonica sex chromosomes.

Task-related functional magnetic resonance imaging-based neuronavigation for the treatment of depression by individualized repetitive transcranial magnetic stimulation of the visual cortex - Zhijun Zhang; Hongxing Zhang; Chun-Ming Xie; Meng Zhang; Yachen Shi; Ruize Song; Xiang Lu; Haisan Zhang; Kun Li; Bi Wang; Yongfeng Yang; Xianrui Li; et al. (Science China Life Sciences, 2021)

Photosynthetic properties and biochemical metabolism of Cucurbita moschata genotypes following infection with powdery mildew - Bi-Hua Chen; Wei-Li Guo; He-Lian Yang; Qing-Fei Li; Jun-Guo Zhou; Xin-Zheng Li (Journal of Plant Pathology, 2020)
Powdery mildew (PM) is one of the most important fungal diseases in Cucurbita moschata (pumpkin) cultivation. This experiment was conducted to shed light on the physiological mechanisms of PM resistance in pumpkin cultivars. PM pathogen was inoculated on pumpkin seedlings, PM-susceptible genotype (JJJD) and PM-resistant genotype (inbred line 112–2) to study the PM-fungal growth, plant photosynthetic and biochemical parameters with different intervals of time. The disease index and pathogen growth observed for the PM-infected 112–2 seedlings were milder than those observed for the JJJD seedlings. The net photosynthetic rate (Pn), stomatal conductance (gs) and transpiration rate (Tr) were reduced for both the PM-infected genotypes, while the internal CO 2 concentration (Ci) increased in comparison with the non-infected controls. PM pathogen inoculation impaired the photosynthetic performance in seedlings of both genotypes and this was largely associated with stomatal closure. In comparison with the non-infected controls, the superoxide dismutase (SOD) and β-1,3-glucanase activities were reduced for both the PM-infected genotypes, while the peroxidase (POD) and phenylalanine ammonia lyase (PAL) activities were increased. The catalase (CAT) activity was reduced in the 112–2 genotype and increased in the JJJD genotype after PM pathogen inoculation. Together, our data show that PM resistance in pumpkin seedlings is associated with the maintenance of photosynthetic performance and the regulation of defense-related enzyme activities .

Two new quinolone alkaloids from the nearly ripe fruits of Tetradium ruticarpum - Yi-Heng Li; Xiao Liu; Min Yin; Fei Liu; Bi Wang; Xu Feng; Qi-Zhi Wang (Natural Product Research, 2020)

Metabolomic profiling on rat brain of prenatal malnutrition: implicated for oxidative stress and schizophrenia - Fei Xu; Xin Li; Weibo Niu; Gaini Ma; Qianqian Sun; Yan Bi; Zhenming Guo; Decheng Ren; Jiaxin Hu; Fan Yuan; Ruixue Yuan; Lei Shi; et al. (Metabolic Brain Disease, 2019)

Direct and legacy effects of herbivory on growth and physiology of a clonal plant - Bi-Cheng Dong; Mo-Zhu Wang; Rui-Hua Liu; Fang-Li Luo; Hong-Li Li; Fei-Hai Yu (Biological Invasions, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Combined effects of soil heterogeneity, herbivory and detritivory on growth of the clonal plant Hydrocotyle vulgaris - Lu Liu; Peter Alpert; Bi-Cheng Dong; Jun-Min Li; Fei-Hai Yu (Plant and Soil, 2017)

NCAM affects directional lamellipodia formation of BMSCs via β1 integrin signal-mediated cofilin activity - Jia-Jia Bi; Jing Li; Bin-Feng Cheng; Hai-Jie Yang; Qiong-Qiong Ding; Rui-Fei Wang; Su-Juan Chen; Zhi-Wei Feng (Molecular and Cellular Biochemistry, 2017)

Identification and Efficiency of a Nitrogen-fixing Endophytic Actinobacterial Strain from Sugarcane - Zhen Wang; Manoj Kumar Solanki; Fei Pang; Rajesh Kumar Singh; Li-Tao Yang; Yang-Rui Li; Hai-Bi Li; Kai Zhu; Yong-Xiu Xing (Sugar Tech, 2017)

Impacts of sediment type on the performance and composition of submerged macrophyte communities - Lin Liu; Xiang-Qi Bu; Jun-Yan Wan; Bi-Cheng Dong; Fang-Li Luo; Hong-Li Li; Fei-Hai Yu (Aquatic Ecology, 2017)

Association Between Osteopontin Gene Polymorphisms and Cerebral Palsy in a Chinese Population - Qing Shang; Chongchen Zhou; Dongzhi Liu; Wenxia Li; Mingjie Chen; Yiran Xu; Fei Wang; Dan Bi; Xiaoli Zhang; Xinzhi Zhao; Lei Wang; Changlian Zhu; et al. (NeuroMolecular Medicine, 2016)

Nontuberculous mycobacterial osteomyelitis - Sheng Bi; Fei-Shu Hu; Hai-Ying Yu; Kai-Jin Xu; Bei-Wen Zheng; Zhong-Kang Ji; Jun-Jie Li; Mei Deng; Hai-Yang Hu; Ji-Fang Sheng (Infectious Diseases, 2015)

Scalar Flux–Gradient Relationships Under Unstable Conditions over Water in Coastal Regions - Zhongkuo Zhao; Zhiqiu Gao; Dan Li; Xueyan Bi; Chunxia Liu; Fei Liao (Boundary-Layer Meteorology, 2013)

Geology, mineralization, and geochronology of the Qianhe gold deposit, Xiong’ershan area, southern North China Craton - Ke-Fei Tang; Jian-Wei Li; David Selby; Mei-Fu Zhou; Shi-Jian Bi; Xiao-Dong Deng (Mineralium Deposita, 2013)

miR-29a and miR-142-3p downregulation and diagnostic implication in human acute myeloid leukemia - Fang Wang; Xiao-Shuang Wang; Gui-Hua Yang; Peng-Fei Zhai; Zhen Xiao; Liang-Yu Xia; Li-Rong Chen; Yu Wang; Xiao-Zhong Wang; Lai-Xi Bi; Nian Liu; Yang Yu; et al. (Molecular Biology Reports, 2012)

Application of seismic anisotropy fluid detection technology in the Ken 71 well block of Shengli Oilfield - Li-Fei Bi; Zhong-Ping Qian; Feng Zhang; Xiao-Yan Chen; Shi-Chun Han; Mark Chapman (Applied Geophysics, 2011)

Effect of atmospheric aerosol on surface ozone variation over the Pearl River Delta region - XueJiao Deng; XiuJi Zhou; Dui Wu; XueXi Tie; HaoBo Tan; Fei Li; XueYan Bi; Tao Deng; DeHai Jiang (Science China Earth Sciences, 2011)

A study of perfectly matched layers for joint multicomponent reverse-time migration - Qi-Zhen Du; Rui-Yan Sun; Tong Qin; Yi-Tong Zhu; Li-Fei Bi (Applied Geophysics, 2010)

Singlet oxygen formation and chlorophyll a triplet excited state deactivation in the cytochrome b 6 f complex from Bryopsis corticulans - Fei Ma; Xiao-Bo Chen; Min Sang; Peng Wang; Jian-Ping Zhang; Liang-Bi Li; Ting-Yun Kuang (Photosynthesis Research, 2009)

A novel drought-inducible gene, ATAF1, encodes a NAC family protein that negatively regulates the expression of stress-responsive genes in Arabidopsis - Ping-Li Lu; Nai-Zhi Chen; Rui An; Zhao Su; Bi-Shu Qi; Fei Ren; Jia Chen; Xue-Chen Wang (Plant Molecular Biology, 2006)